Analisis Komparatif dalam Penerapan Pertanian Konservasi terhadap Pendapatan Usahatani Jeruk di Kecamatan Miomaffo Barat - Maria Yanti Akoit; Elfrida Desiderata Naihati; Maria Yustingsih (Fakultas Pertanian, Universitas Timor, 2019)
This research is aimed to know the comparison on the implementation of agricultural conservation system against the income of orange farming in Saenam village, the district of West Miomaffo, North of Central Timor regency of East Nusa Tenggara province. The method used is survey which is located in Saenam village. The choice of the location was based on purposive sampling. Method analysis is Chi Square. The result of the analysis shows that Chi Kuadrat test = 13,33 at df = 2 is more than chi kuadrat table at significance level 5% = 5,991 and significance level 1% = 9,210 or the value of significance level (Asymp.Sig.(2- sided) 0,001 lower at α = 0,05 as well as α = 0,01. The result shows that there is a difference of cost in the activity of orange farming. The result of the analysis shows that Chi Kuadrat test = 33,191 at df = 2 is more than chi kuadrat table at significance level 5% = 5,991 and significance level 1% = 9,210 or the value of significance level (Asymp.Sig.(2- sided) 0,000 lower at α = 0,05 as well as α = 0,01. The result shows that there is a difference of cost and income in the activity of orange farming.